Resistin protects against 6‐hydroxydopamine‐induced cell death in dopaminergic‐like MES23.5 cells. Issue 3 (23rd November 2012) - Lu, Dah‐Yuu; Chen, Jia‐Hong; Tan, Tzu‐Wei; Huang, Chih‐Yang; Yeh, Wei‐Lan; Hsu, Horng‐Chaung
Abstract Resistin is originally reported as an adipose tissue‐specific hormone and is thought to represent a link between obesity and insulin‐resistant diabetes. Adipokines exert energy‐regulation and has been reported to have neuroprotective effect like leptin, adiponectin, and ghrelin. However, the role of resistin in neuroprotective effect has not been explored. 6‐hydroxydopamine (6‐OHDA), one of the most investigated Parkinson's disease neurotoxins, is widely used to study mechanisms of cell death in dopaminergic neurons. In the present study, our results show that treatment of resistin protects 6‐OHDA‐induced cell death in dopaminergic‐like MES23.5 cells. Resistin also antagonizes 6‐OHDA‐induced apoptotic cell death measured by fluorescence‐activated cell sorter (FACS) analysis and Hochest 33342 staining. Furthermore, treatment of resistin also dramatically reduces 6‐OHDA‐mediated ROS production and mitochondria transmembrane potential dissipation. Moreover, expression of 6‐OHDA‐induced apoptotic markers, such as Bcl‐2 degradation, Bax expression, PARP degradation and caspase 3 activity increase, are all attenuated by resistin treatment. Our results also show that resistin induces up‐regulation of heat shock protein (Hsp) 32 (heme oxygenase‐1, HO‐1) and Hsc (heat shock cognate) 70. The protective effect of resistin on 6‐OHDA‐induced cell death is abolished by HO‐1 inhibitor zinc protoporphyrin IX and HSP inhibitor KNK437. These results suggest the neuroprotective effects of resistin against 6‐OHDA‐induced cell death with the underlying mechanisms of inhibiting oxidative stress and apoptosis. Therefore, we suggest that resistin may provide a useful therapeutic strategy for neurodegenerative diseases such as Parkinson's disease. J. Cell. Physiol. 228: 563–571, 2013. © 2012 Wiley Periodicals, Inc.